Konsep Keimanan dan Dosa Besar: Perspektif Khawarij, Murji’ah, Mu’tazilah, dan Dua Madzhab Kalam Sunni - Yanto Maulana Restu; Muhammad Zaky Jauhar Fauzi; Alya Tri Nurmala Sari; Yeni Nuryani; Aam Maisatul Mubarokah; Ahmad Zaky Abdullah (An-Nahdloh: Journal of Education and Islamic Studies, 2026)
This article examines the concepts of faith and major sins from the perspective of four major schools of Islamic thought: the Khawarij, the Murji'ah, the Mu'tazilah, and the two Sunni schools of Kalam (Ash'ari and Maturidi). This study highlights the differences in views regarding the definition of faith, the limits, and consequences of major sins, as well as their positions on the perpetrators of major sins within the framework of Islamic theology and ethics. The Khawarij view faith as an absolute, inherent belief and consider major sins to be disbelief, while the Murji'ah emphasize that faith is a conviction of the heart that remains despite committing major sins, and that punishment is left to God. The Mu'tazilah affirm God's justice and consider major sins as forgivable violations of faith, while Sunni schools such as the Ash'ari and Maturidi argue that faith encompasses conviction of the heart and deeds, and that the perpetrator of major sins does not deviate from faith if he repents. This study offers a comparative analysis that enriches understanding of these differences in theological interpretations in the context of faith and sin in Islam. Keywords: faith, sin, theology, madzhab, Ash'ari